Pengaruh Dukungan Sosial Terhadap Penyesuaian Diri Pada Siswa Smp Muhammadiyah Ajibarang - Hamzah, Imam Faisal; Rahardjo, Pambudi; Wahidah, Fatin Rohmah Nur (Universitas Muhammadiyah Purwokerto, 2023)
This study aims to determine the effect of social support on adjustment in SMP Muhammadiyah Ajibarang students. This study uses a quantitative method with a scale of social support and adjustment. The research population was students of SMP Muhammadiyah Ajibarang with a sample of 110 students. The validity test in this study used the product moment, while the reliability test used the alpha cronbach technique. The social support scale has a reliability of 0.895 and the self-adjustment scale has a reliability of 0.901. The data technique used in this study is a simple regression analysis technique to determine the effect of social support on self-adjustment of SMP Muhammadiyah Ajibarang students. Based on the analysis of the data obtained, the Fcount value is 140,668 with p = 0.000 (p <0.05). From the results of data analysis at a significance level of 5%, a significant value was obtained (p) = 0.000 (p <0.05) so that the hypothesis proposed was accepted, namely was a significant influence between social support on self-adjustment in SMP Muhammadiyah Ajibarang students.